Moving Further Beyond Secularism: A “Lutheran” Reading of the Cosmology of Thomas Nagel - Fehige, Yiftach (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2018)
Thomas Nagel has proposed a highly speculative metaphysical theory to account for the cosmological significance that he claims the human mind to have. Nagel argues that the mind cannot be fully explained by Darwinian evolutionary theory, nor should theological accounts be accepted. What he proposes instead is an explanation in terms of cosmological non-purposive teleological principles. Our universe awakens to itself in each and every individual consciousness. What comes to light in a pronounced manner when consciousness arises, are the mental aspects of the stuff that the universe is made of. These mental aspects are always concurrently present with the physical aspects of the basic elements that constitute the universe. This paper situates Nagel’s cosmology in the context of discussions of the relationship between modern science and Christian theology. It focuses on the history of modern science’s efforts to locate the origins of humanity. The aim of the paper is to present a qualified “Lutheran” reading of Nagel’s theory of the cosmological significance of the human mind. This will unearth strong reasons to think that Nagel’s cosmology is less secular than it claims to be.